Analysis Super (a; d)-S3 Antimagic Total Dekomposition of Helm Graph Connektive for Developing Ciphertext - Kholifatur Rosyidah; Dafik Dafik; Susi Setiawani (jcgant, 2020)
Covering of G is H = fH1; H2; H3; :::; Hkg subgraph family from G with every edges on G admit on at least one graph Hi for a i 2 f1; 2; :::; kg. If every i 2 f1; 2; :::; k g, Hi isomorphic with a subgraph H, then H said cover-H of G. Furthermore, if cover-H of G have a properties is every edges G contained on exactly one graph Hi for a i 2 f1; 2; :::; kg, then cover-H is called decomposition-H. In this case, G is said to contain decomposition-H. A graph G(V; E) is called (a; d)-H total decomposition if every edges E is sub graph of G isomorphic of H. In this research will be analysis of super (a; d)-S3 total decomposition of connective helm graph to developing ciphertext.Key Word : Super (a; d)-S3, Dekomposisi, Graf helm, dan Ciphertext